Nanoestruturas de óxido de zinco : síntese e avaliação antitumoral em câncer de bexiga - Jesus, Jeanne Louise Fernandes (2021)
In recent years, the interest in zinc oxide nanostructures (ZnONPs) has grown due to properties such as biocompatibility, chemical stability and selective cytotoxicity against tumor cells, become them promising for application in the biomedical area. In order to evaluate the antitumor activity in different morphologies, this study aimed to develop ZnO nanostructures and evaluate its biological response (antitumor activity) with T24 cells (bladder cancer cells). ZnONPs were synthesized by two methods: coprecipitation method and hydrothermal method and characterized by FESEM, TEM, XRD, TGA and ICP techniques. Furthermore, the results of the zeta potential, MTT and NMA analyses provided support for the elaboration of a toxicity map of the synthesized nanostructures. The ZnONPs showed predominantly blade, rod and flower morphologies. The MTT assay showed that the zinc oxide nanostructures exhibited a biocompatibility profile against Vero cells (experimental model of normal cells) and anticancer activity against T24 cells (concentration of 200 µg/mL), indicating potential application in the oncological area for the treatment of human bladder cancer. Although there is a need for further studies to elucidate some cellular mechanisms related to exposure to nanostructures, the results obtained, even in preclinical experimental character, safely potentiated the use of zinc oxide nanostructures as a tool for the treatment of cancer of human bladder.